Sublating humanism - Rošker, Jana S. (Asian studies, 2024)
Chinese humanism developed distinctly from European humanist discourses, reflecting unique cultural and philosophical traditions. Analysing these differences can enhance our understanding of both the specific characteristics of Chinese humanism and the diverse potentialities within contemporary global humanist thought. This comparative perspec-tive, enhanced by employing the method of sublation, underscores the planetary relevance of humanism. It demonstrates how diverse cultural perspectives enrich and broaden the scope of global discourse, leading to a more inclusive understanding of humanism world-wide. In this paper I will give a brief historical overview of the origins and development of the formation of ideas which, in China, placed the human being at the centre of culture and the cosmos. But in order to better understand the differences that demarcate Chi-nese views of humans and their position in the world from European ones, we will first look at how the relationship between people and the communities in which they live is structured in the Chinese tradition. We will then examine the political and philosophical currents shaping Confucian discourse and take a look on the way in which each of them contributes to the Chinese model of humanism. By applying the method of sublation, we intend to investigate how these two systems could complement and enhance each other, thereby helping to establish a foundational framework for a newly proposed transcultural planetary ethics.
Keywords: Chinese humanism; Confucian relationism; filozofsko konfucijanstvo; kitajski humanizem; konfucijanski relacionizem; philosophical Confucianism; planetarna etika; planetary ethics; political Confucianism; politični konfucianizem